The relationship between profitability ratios and market reactions to M&A announcements - Machado, Pedro Afonso Gonçalves Alvelas (2022)
In this dissertation, we examine the relationship between profitability ratios and abnormal returns around mergers and acquisitions’ announcements, using a sample of 341 transactions completed in the United States between 2010 and 2019. We aimed to investigate the targets and the acquirers, not only observing the investors’ reactions to the profitability levels of the opposite firm but also by noticing if there is any relationship with the direct comparison between both companies. The results show that there is no significant relationship between the acquirers’ cumulative abnormal returns and the targets’ profitability indicators except the GPM. Moreover, when we change the explanatory variable to the difference between profitability levels of both participants in the transaction there is no significant relationship whatsoever. On the other hand, the targets’ cumulative abnormal returns show a significant relationship with the acquirers’ NPM, GPM and ROA and when we change the explanatory variable, as previously mentioned, the EPS also becomes a significant measure.